Discovering Psalms content, interpretation, reception - Creach, Jerome F. D. 1962- (La Vergne SPCK, 2020)
Intro -- Contents -- Acknowledgements -- Abbreviations -- Introduction: The role of the Psalms in the life of the Church -- The nature and purpose of this book -- A preview of the book -- Part 1 Issues in reading the Psalms and the Psalter -- 1 What is a psalm? -- Titles for the book -- How many psalms? -- Anatomy of a psalm -- The heading -- The body of a psalm -- Colophon -- Translation -- Collections and clusters of psalms -- The structure of the book -- Introductory psalms: Psalms 1 and 2 -- Concluding psalms: Psalms 146-150 -- Fivefold division -- 2 It's poetry! -- What is poetry and why is it important? -- Important terms -- What makes the Psalms poetry? -- Semantic parallelism -- Lowth's categories of parallelism -- Synonymous -- Antithetical -- Synthetic -- Refining the categories -- Intensification -- Complementarity -- Consequential statements -- Metaphor -- The Lord is king -- Refuge -- Simile: another powerful figure of speech -- As a deer longs for water -- Like a tree -- 3 Did David write the Psalms? -- Claims of Davidic authorship -- Psalm 3 as a starting point -- Other affirmations of David as author of the Psalms -- Questioning David as author of the Psalms -- Psalm 72 as turning point in Davidic authorship -- Figurative readings of David in the Psalms -- If not David, then who? -- Recovering David in the Psalms -- 4 A psalm for every occasion: types of psalms -- Psalms study in the twentieth century -- Hermann Gunkel and the rise of form criticism -- Types of psalms -- 1 Prayers for help by an individual -- Subcategory: song of trust -- 2 Prayers for help by the community -- 3 Hymns of praise -- Language and style of hymns -- Imperative -- Description of God's mighty deeds -- Hymns according to subject matter -- Creation hymns -- Enthronement psalms -- Zion songs -- Historical hymns -- 4 Thanksgiving songs of the individual.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books